Genetic exchange mechanisms in Neisseria gonorrhoeae. - Norlander, L (1979)
There are two mechanisms for genetic exchange in Neisseria gonorrhoeae. Plasmid deoxyribonucleic acid can be transferred by conjugation, which is dependent on the presence of a 24.5-megadalton plasmid in the donor cell. We have shown that chromosomal deoxyribonucleic acid can be exchanged between all colonial variants by transformation, but not by conjugation. In the nonpiliated variants, however, this exchange was dependent on the presence of the 24.5-megadalton plasmid in the recipient cell.